Community-based Landscape Planning in Kampong Batu Lonceng within Lembang Faults Mitigation Framework - Faisal, Budi; Dahlan, Mohammad Zaini; Martokusumo, Widjaja; Rani, Medria Shekar; Purwaningsih, Rr Diah Asih; Rahmy, Widyastri Atsary; Binta, Izaza; Pamumpuni, Astyka; Meilano, Irwan; Kobayashi, Hirohide; Shibata, Shozo; Purwaningrum, Rr Diah Asih (Jurnal Lanskap Indonesia, 2025)
Lembang Fault is one of the active faults produced by the subducted Indo-Australian plate beneath the Eurasian plate along Java Island. It has a high potential for hazard due to its proximity to densely populated areas, including Kampong Batu Lonceng, located approximately 150 meters from the fault. This paper explores the interplay between philosophical beliefs, emotional attachment to the land, natural hazards, land availability for relocation, and applicable regulations in Kampong Batu Lonceng. A three-phase landscape planning regarding the Kampong settlement disaster mitigation was proposed based on data collected from the community stakeholders through field surveys, initial interviews, and discussion. The first phase proposed that the community stays in the existing area with minor preventive developments. The second phase proposed that the community moves across the river and move further to a new, safer location in the third phase. The first phase is the most reasonable since the community does not have to move to another location but needs to revitalize the forest. The second and third phases can only be pursued when the community understands the potential disaster of the fault. Moreover, the third phase requires that the government provide a safer zone for the community to relocate. Another discussion with the community stakeholders shows an agreement towards the first and the third phases and a reluctance over the second phase. However, although many regulations have already taken place formally, enforcing them towards implementation in a traditional community needs to be handled very carefully.